2013
DOI: 10.1517/14728222.2013.783571
|View full text |Cite
|
Sign up to set email alerts
|

EGFR mutational status in penile cancer

Abstract: The most frequent activating EGFR mutations detected in non-small setting lung cancer are absent in penile cancer (PC). Sequencing of the entire EGFR gene in patients with PC may provide useful insights, as its mechanism of overexpression and activation in PC remains unknown.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 20 publications
0
11
0
Order By: Relevance
“…EGFR overexpression appeared to be universal and correlated with the grade of penile SCCs, and the expression of phosphorylated EGFR was recently found to be strongly related to an increase in the risk of recurrence and shorter overall survival in patients with N0-1 disease [5][6][7].…”
Section: Discussionmentioning
confidence: 98%
“…EGFR overexpression appeared to be universal and correlated with the grade of penile SCCs, and the expression of phosphorylated EGFR was recently found to be strongly related to an increase in the risk of recurrence and shorter overall survival in patients with N0-1 disease [5][6][7].…”
Section: Discussionmentioning
confidence: 98%
“…In a literature review of individual data of 28 patients with advanced penile cancer receiving anti-EGFR monoclonal antibodies (cetuximab, panitumumab, and nimotuzumab), a 50% radiological response rate was achieved, but a median PFS of only approximately 3 months (interquartile range, 1.5–5.78, Di Lorenzo et al, 2015). From a biological perspective, EGFR appears a promising target in penile cancer, as it is universally expressed and frequently phosphorylated (Di Lorenzo et al, 2013a), but infrequently amplified (Di Lorenzo et al, 2013a), or mutated (Di Lorenzo et al, 2013b), while mutations of downstream signaling proteins (such as KRAS/BRAF) are rare (Gou et al, 2013). Nevertheless, we failed to identify a signal of prolonged OS associated with the use of cetuximab in our study cohort.…”
Section: Discussionmentioning
confidence: 99%
“…Two studies found that the presence of LNMs is higher for patients with human papillomavirus DNA-negative; however, the P values are not significant 1819. P53, Ki-67, E-cadherin, and epidermal growth factor receptor (EGFR) are suggested molecular prognostic markers in PSCC by some studies 16202122. Di Lorenzo et al 21.…”
Section: Discussionmentioning
confidence: 99%